Synthesis and Applications of Chelating Resins of Polysaccharides Containing Hydroxamic Acid - Bohra, Sunita; Kanungd, Neeta; Mathur, P.N. (Asian Journal of Chemistry, 2010)
Chelating agents find great utility in mineral processing and in hydrometallurgical processes. Polymeric chelating agents have replaced the chelating agents. Hydroximates are useful in mineral processing as collectors for various mineral systems containing Ti,Y,La,Ce,Nb, Ta, Sn, W, Fe, Mn and Cu. Resins containing hydroxamic acid group will be more efficient. Synthesis of hydrophillic chelating resins of polysaccharide guaran incorporated with hydroxamic acids of fatty and amino acids is reported. Physicochemical characteristics of the newly synthesised resins are also reported. The amount of retention of metal by resin at equilibrium, has been determined in terms of distribution coefficient (λ1 or Kd). Kd values for Fe(II), Cu(II), Ni(II), Co(II) and U(VI) systems with the newly synthesised resins are reported.